2012
DOI: 10.1159/000337908
|View full text |Cite
|
Sign up to set email alerts
|

A Case of KIT-Negative Extra-Gastrointestinal Stromal Tumor of the Lesser Omentum

Abstract: We report the unique case of a 69-year-old man with an extra-gastrointestinal stromal tumor (EGIST) in the lesser omentum. Based on the location of the tumor and the radiological findings, we made a provisional diagnosis of hepatic cavernous hemangioma in the lateral segment. However, after 5 years of follow-up, tumor growth was noted and the patient underwent a laparotomy. The tumor was located in the lesser omentum and resected en bloc with its fused lesser omentum and an adherent portion of the liver. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Literature search of MEDLINE was performed for all articles in English published from 1998 through 2015. MEDLINE search resulted in 47 case reports 8 9 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 including 57 patients and 6 case series 61 62 63 64 65 66 including 40 cases. As a result, a total of 99 omental GISTs patients were identified.…”
Section: Methodsmentioning
confidence: 99%
“…Literature search of MEDLINE was performed for all articles in English published from 1998 through 2015. MEDLINE search resulted in 47 case reports 8 9 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 including 57 patients and 6 case series 61 62 63 64 65 66 including 40 cases. As a result, a total of 99 omental GISTs patients were identified.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Ogawa et al [8] have reported a case of EGIST of the lesser omentum, which was initially classified as a benign liver tumor (hemangioma or INF); at histological examination it was, curiously as in our case, an epithelioid subtype, with CD117 negative. These facts could suggest a possible correlation between uncommon pathological features and atypical radiological appearances that, in our opinion, should be investigated.…”
Section: Accepted Manuscriptmentioning
confidence: 59%
“…[5]22MGIST of the stomach27SpindleUnknownOgawa et al . [6]69MHepatic hemangioma80EpithelioidNoneSkandalos et al . [10]79FTumor of the pancreas110SpindleNoneTrombatore et al .…”
Section: Discussionmentioning
confidence: 99%